The problem of prediction in modern seismology: Epistemological aspects and science policy issues - Katsaloulis, Iraklis (Neusis, 2025)
Earthquake prediction is a relatively new field, in which many important questions remain open, as the relevant scientific knowledge is characterized by a high degree of uncertainty and is far from being considered well established. Nevertheless, it is an area of science that is directly linked to political decision-making for the protection of human life and property, as modern societies, with the creation of large cities and potentially dangerous infrastructures, such as nuclear reactors for example, are vulnerable to the consequences of a strong earthquake. This article will briefly present the debate on earthquake prediction using the methodology of Science and Technology Studies (STS), in order to highlight both epistemological issues and public policy issues, as well as the ways in which they affect each other.